OUTBREAK INVESTIGATION OF DENGUE FEVER IN SUNDIA, CHAKAISER, SHANGLA, PAKISTAN-2008 - Murad, Nighat; Asghar, Rana Jawad; Zaheen, Mohammad; Shawali, Rashda (Journal of Ayub Medical College Abbottabad, 2014)
Background: From October 1-6, 2008 media reported increased fever cases along-with some deaths in a village that were found positive for dengue IgM antibody. The provincial health authorities ordered an investigation. Our investigation aimed to determine the magnitude of disease, understand the epidemiological characteristics, and recommend preventive measures. Methods: The study was to investigate an epidemic through a descriptive study followed by a case-control study in the village Sundia from October 14th to Nov 2nd, 2008. A case defined as: Anyone from the village with fever and any one of the symptoms including bone breaking fever (arthralgia, myalgia), rash, bleeding from nose and gums from 21st Sept 2008 to 2nd Nov 2008. For comparison, controls (n=183) i.e., those who did not fulfil the case definition criteria: Systematic random sampling technique was used and data was collected on a pro forma. Blood samples were also collected from those who had fever for the last 3 days or more. Results: A total of 113 (33%) households were surveyed out of 339 among which 156 (46%) cases were selected based on case definition and all the rest (183) were taken as controls. There were 84 (54%) males and 72 (46%) females. Mean age was 30 (range between 1-80 years). Beside fever, other predominant symptoms were joint pains 94 (60%) and headache 91 (58%). Seventy samples were collected and tested for dengue IgM on ELISA method and 12 (17.14%) were found positive. Logistic regression was done and uncovered water containers (p-value <0.05) to (adjusted OR=1.8; p=0.008), surrounding marshy land (p=0.03) to (adjusted OR=1.75; p=0.02) & tap water (p=0.001) to (adjusted OR=3.2964; p=0.0012) were found to be associated with the fever. Conclusions: Investigation showed presence of different risk factors which also pertain to other countries. The gaps in communication lead to the increased number of fever cases. Dengue prevention and control program, capacity building and a strong surveillance system is crucial. Keywords: Dengue, Shangla, KPK, Arthralgia, Myalgia